Altered cytokinin metabolism affects cytokinin, auxin, and abscisic acid contents in leaves and chloroplasts, and chloroplast ultrastructure in transgenic tobacco - Polanská, Lenka; Vicánková, Anna; Nováková, Marie; Malbeck, Jirí; Dobrev, Petre I; Brzobohaty, Bretislav; Vanková, Radomíra; Machácková, Ivana (Journal of experimental botany, 2007)
Cytokinins (CKs) are involved in the regulation of plant development including plastid differentiation and function. Partial location of CK biosynthetic pathways in plastids suggests the importance of CKs for chloroplast development. The impact of genetically modified CK metabolism on endogenous CK, indole-3-acetic acid, and abscisic acid contents in leaves and isolated intact chloroplasts of Nicotiana tabacum was determined by liquid chromatography/mass spectrometry and two-dimensional high-performance liquid chromatography, and alterations in chloroplast ultrastructure by electron microscopy. Ectopic expression of Sho, a gene encoding a Petunia hybrida isopentenyltransferase, was employed to raise CK levels. The increase in CK levels was lower in chloroplasts than in leaves. CK levels were reduced in leaves of tobacco harbouring a CK oxidase/dehydrogenase gene, AtCKX3. The total CK content also decreased in chloroplasts, but CK phosphate levels were higher than in the wild type. In a transformant overexpressing a maize beta-glucosidase gene, Zm-p60.1, naturally targeted to plastids, a decrease of CK-O-glucosides in chloroplasts was found. In leaves, the changes were not significant. CK-O-glucosides accumulated to very high levels in leaves, but not in chloroplasts, of plants overexpressing a ZOG1 gene, encoding trans-zeatin-O-glucosyltransferase from Phaseolus lunatus. Manipulation of the CK content affected levels of indole-3-acetic and abscisic acid. Chloroplasts of plants constitutively overexpressing Sho displayed ultrastructural alterations including the occasional occurrence of crystalloids and an increased number of plastoglobuli. The other transformants did not exhibit any major differences in chloroplast ultrastructure. The results suggest that plant hormone compartmentation plays an important role in hormone homeostasis and that chloroplasts are rather independent organelles with respect to regulation of CK metabolism.
Keywords: listy rostlin; Oxidoreductases; Abscisic Acid; chloroplasty; kukuřice setá; beta-Glucosidase; fazol; kyseliny indoloctové; Chloroplasts; Plant Proteins; oxidoreduktasy; Cytokinins; Zea mays; Petunia; cytokininy; Plants, Genetically Modified; Nicotiana; Indoleacetic Acids; Microscopy, Electron, Transmission; glukosyltransferasy; Phaseolus; Plant Leaves; geneticky modifikované rostliny; Alkyl and Aryl Transferases; Glucosyltransferases; beta-glukosidasa; tabák; kyselina abscisová; transmisní elektronová mikroskopie; alkyltransferasy a aryltransferasy; rostlinné proteiny